Intake of glucosinolates and risk of coronary heart disease in three large prospective cohorts of US men and women - Ma, Le (Clin Epidemiol, 2018)
IMPORTANCE: Glucosinolates, a group of phytochemicals abundant in cruciferous vegetables, may have cardioprotective properties. However, no prospective study has evaluated the association of intake of glucosinolates with the risk of coronary heart disease (CHD). OBJECTIVE: The objective of the study was to evaluate the association between the intake of glucosinolates and incident CHD in US men and women. DESIGN: Prospective longitudinal cohort study. SETTING: Health professionals in the USA. PARTICIPANTS: We followed 74,241 women in the Nurses’ Health Study (NHS; 1984–2012), 94,163 women in the NHSII (1991–2013), and 42,170 men in the Health Professionals Follow-Up Study (1986–2012), who were free of cardiovascular disease and cancer at baseline. EXPOSURE: Glucosinolate intake was assessed using validated semi-quantitative food frequency questionnaires at baseline and updated every 2–4 years during follow-up. MAIN OUTCOME MEASURES: Incident cases of CHD were confirmed by medical record review. RESULTS: During 4,824,001 person-years of follow-up, 8,010 cases of CHD were identified in the three cohorts. After adjustment for major lifestyle and dietary risk factors of CHD, weak but significantly positive associations were observed for glucosinolates with CHD risk when comparing the top with bottom quintiles (hazard ratio [HR]:1.09; 95% CI: 1.01, 1.17; P(trend)<0.001). Higher intakes of three major subtypes of glucosinolates were consistently associated with a higher CHD risk, although the association for indolylglucosinolate did not achieve statistical significance. Regarding cruciferous vegetable intake, participants who consumed one or more servings per week of Brussels sprouts (HR: 1.16; 95% CI: 1.06, 1.26; P<0.001) and cabbage (HR: 1.09; 95% CI: 1.02, 1.17; P=0.009) had a significantly higher CHD risk than those who consumed these cruciferous vegetables less than once per month. CONCLUSION AND RELEVANCE: In these three prospective cohort studies, dietary glucosinolate intake was associated with a slightly higher risk of CHD in US adults. These results warrant replications in further studies including biomarker-based studies. Further studies are needed to confirm these findings and elucidate mechanistic pathways that may underlie these associations.